2018
DOI: 10.1016/j.amjsurg.2018.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Complications, length of stay, and cost of cholecystectomy in kidney transplant recipients

Abstract: We hypothesized that cholecystectomy may be riskier for kidney transplant recipients (KTR) given their lifelong immunosuppression, physiologic impact of renal failure, and increased risk of gallstone and biliary disease. Using NIS, we compared mortality, morbidity, length of stay and cost in KTR vs non-KTR following cholecystectomy in the US from 2000 to 2011, adjusting for patient and hospital level factors, including transplant center status. Mortality was higher (OR 2.4), morbidity was higher (OR 1.3), LOS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…DiBrito et al compared mortality following appendectomy, cholecystectomy, and colorectal resections in kidney transplant recipients with that of nontransplant patients and found that mortality was similar for appendectomy but higher for cholecystectomy (2.7% versus 1.2%, adjusted OR 2.39, 95% CI 1.66-3.44) and colorectal resections (11.1% versus 4.3%, adjusted OR 2.68, 95% CI 3.59-4.81) in transplant recipients. [23][24][25] However, these studies included elective operations and lacked data on the indication for surgery and therefore were not limited to EGS conditions. Moreover, patients undergoing nonoperative management for EGS conditions were excluded from the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…DiBrito et al compared mortality following appendectomy, cholecystectomy, and colorectal resections in kidney transplant recipients with that of nontransplant patients and found that mortality was similar for appendectomy but higher for cholecystectomy (2.7% versus 1.2%, adjusted OR 2.39, 95% CI 1.66-3.44) and colorectal resections (11.1% versus 4.3%, adjusted OR 2.68, 95% CI 3.59-4.81) in transplant recipients. [23][24][25] However, these studies included elective operations and lacked data on the indication for surgery and therefore were not limited to EGS conditions. Moreover, patients undergoing nonoperative management for EGS conditions were excluded from the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…58 Last, immunosuppression and underlying comorbidities make transplant recipients also more susceptible to infectious, cardiovascular, and respiratory complications. 23,24 Additional research is required to elucidate the modifiable risk factors associated with an increased risk of death after EGS events in SOTRs. Where the patient received care (transplant versus, nontransplant hospital) and involvement of transplant physicians also warrant further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although prior studies have sought to characterize the volume and outcomes of transplant recipients requiring EGS operations, they are largely limited to single centers or evaluate single conditions [ 5 , [7] , [8] , [9] ]. Additionally, data regarding the cost burden of hospitalizations and readmissions, is lacking.…”
Section: Introductionmentioning
confidence: 99%